Differentiating stroke and movement accelerometer profiles to improve prescription of tennis training drills - Perri, T.; Reid, M.; Murphy, A.; Howle, K.; Duffield, R. (The Journal of Strength and Conditioning Research, 2023)
This study compared the movement- and stroke-related accelerometer profiles and stroke counts between common on-court tennis training drills. Ten, junior-elite, male tennis players wore a cervical-mounted global positioning systems, with in-built accelerometer, gyroscope, and magnetometer during hard court training sessions (n = 189). Individual training drills were classified into 8 categories based on previous research descriptions. Manufacturer software calculated total player load (tPL), while a prototype algorithm detected forehand (FH), backhands (BH), and serves and then calculated a stroke player load (sPL) from individual strokes. Movement player load (mPL) was calculated as the difference between tPL and sPL. Drill categories were compared for relative (.min-1) tPL, sPL, mPL, and stroke counts via a 1-way analysis of variance with effect sizes (Cohen's d) and 95% confidence intervals. Highest tPL.min-1 existed in accuracy and recovery or defensive drills (p < 0.05), with lowest tPL·min-1 values observed in match-play simulation (p < 0.05). For sPL·min-1, accuracy drills elicited greater values compared with all other drill types (p < 0.05), partly via greater FH-sPL·min-1 (p < 0.05), with lowest sPL·min-1 existing for match-play (p < 0.05). Accuracy, open, and recovery or defensive drills result in greater BH-sPL·min-1 and BH.min-1 (p < 0.05). Serve-sPL·min-1 is highest in technical and match-play drills (p < 0.05). Higher mPL·min-1 existed in accuracy, recovery or defensive, 2v1 net, open, and 2v1 baseline (p < 0.05). Furthermore, mPL·min-1 in points drills was greater than technical and match-play simulation drills (p < 0.05). Higher hitting-based accelerometer loads (sPL·min-1) exist in accuracy drills, whereas technical and match-play drills show the lowest movement demands (mPL·min-1). These findings can aid individual drill prescription for targeting movement or hitting load.